DAT gene polymorphisms (rs28363170, rs393795) and levodopa-induced dyskinesias in Parkinson's disease. (18th January 2019) - Purcaro, Carlo; Vanacore, Nicola; Moret, Federica; Di Battista, Maria Elena; Rubino, Alfonso; Pierandrei, Silvia; Lucarelli, Marco; Meco, Giuseppe; Fattapposta, Francesco; Pascale, Esterina
Highlights: rs28363170 and rs393795 variants of the DAT gene, with LID occurrence in PD was studied. No association was found between PD patients with or without LID and the single polymorphisms. The combination of the 10R/10R and A carrier reduces the risk of dyskinesia by 81%, adjusted for clinical and pharmacological variables. Abstract: L-dopa–induced dyskinesias (LID) is a common motor side effect of levodopa therapy of Parkinson's disease (PD). The identified predictors may only partially account for the risk of developing LID and genetic factors may contribute to this variability. The present study is aimed to investigate whether polymorphisms in the dopamine transporter gene ( DAT ) are associated with the risk of developing LID. Genotyping of the 40-bp VNTR (rs28363170) and rs393795 (A/C) polymorphisms of the DAT gene was performed in a well-characterized cohort of 181 Italian PD patients in treatment with L-DOPA for 3 years or more. The results of our study show that there is no difference in dyskinesias prevalence among carriers of the two DAT gene polymorphisms. However, the combination of the two genotypes 10R/10R (rs28363170) and A carrier (rs393795) of the DAT gene reduces the risk of LID occurrence during long-term therapy with l -DOPA with respect to the PD subjects who did not carry these alleles (OR = 0.31; 95% CI, 0.09-0.88). Also based on a logistic regression analysis, the 10R/10R and the A carrier allele of the rs393795 polymorphisms of the DAT gene, could reduce the susceptibility to develop LID during levodopa therapy adjusted by demographical and clinical variables (OR = 0.19; 95% CI, 0.05-0.69). Additional studies further investigating the rs28363170 and rs393795 polymorphisms with LID in PD are needed to clarify their role in different ethnicities.